1998
DOI: 10.1016/s1078-5884(98)80041-5
|View full text |Cite
|
Sign up to set email alerts
|

The ability of qualitative assessment of the common femoral doppler waveform to screen for significant aortoiliac disease

Abstract: Visual interpretation of the common femoral Doppler waveform is a sensitive and accurate technique for the prediction of significant aortoiliac stenosis. It is of particular value when full ultrasound aortoiliac assessments are not feasible due to time constraints, obesity or the presence of bowel gas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 27 publications
0
34
0
Order By: Relevance
“…The sensitivity of the monophasic CFA waveform for significant iliac stenosis in our study was 57%. The quoted sensitivities of monophasic waveforms across the literature vary from 56 to 98% [6,7,10]. Given that it has previously been shown that Doppler waveforms can normalise at sufficient distances from the site of a stenosis, it is not entirely surprising that this is the case [10,11].…”
Section: Discussionmentioning
confidence: 99%
“…The sensitivity of the monophasic CFA waveform for significant iliac stenosis in our study was 57%. The quoted sensitivities of monophasic waveforms across the literature vary from 56 to 98% [6,7,10]. Given that it has previously been shown that Doppler waveforms can normalise at sufficient distances from the site of a stenosis, it is not entirely surprising that this is the case [10,11].…”
Section: Discussionmentioning
confidence: 99%
“…Visual interpretation of the waveform shape may differentiate between normal and abnormal vascular flow, 6,7 but such interpretation is qualitative and subjective. To quantitatively and objectively describe how the normal triphasic waveform of the lower extremity changes into the monophasic or nonpulsatile waveform indicating ischemia was the goal of this study.…”
Section: Discussionmentioning
confidence: 99%
“…The arterial fl ow recorded is altered in the event of constriction following a certain reduction in lumen diameter [16,30,31]. Changes in Doppler waveforms morphology with regard to stenosis are known as direct signs.…”
Section: Changes In Doppler Waveforms Morphology Depending On the Degmentioning
confidence: 99%